2010
DOI: 10.1038/ng.604
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide meta-analyses identifies seven loci associated with platelet aggregation in response to agonists

Abstract: Platelet function mediates both beneficial and harmful effects on human health, but few genes are known to contribute to variability in the process. We tested association of 2.5 million SNPs with platelet aggregation responses to 3 agonists (ADP, epinephrine and collagen) in two European-ancestry cohorts (N ≤ 2,753 in the Framingham Heart Study, N ≤ Users may view, print, copy, download and text and data-mine the content in such documents, for the purposes of academic research, subject always to the full Condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
262
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 248 publications
(274 citation statements)
references
References 48 publications
11
262
1
Order By: Relevance
“…19,[28][29][30] Interestingly, MRVI1 on chr11, another locus previously associated with platelet aggregation, 31 showed genetic overlap between migraine and IS, adding to previous data suggesting a shared role of platelet dysfunction in migraine and IS. 9 Mendelian randomization studies and interventional studies are needed to determine the exact role of platelets in mediating such genetic risk.…”
Section: Discovery Setmentioning
confidence: 85%
“…19,[28][29][30] Interestingly, MRVI1 on chr11, another locus previously associated with platelet aggregation, 31 showed genetic overlap between migraine and IS, adding to previous data suggesting a shared role of platelet dysfunction in migraine and IS. 9 Mendelian randomization studies and interventional studies are needed to determine the exact role of platelets in mediating such genetic risk.…”
Section: Discovery Setmentioning
confidence: 85%
“…Interestingly, IRAG mutant platelets showed hyperaggregability upon agonist activation. Polymorphisms of Mrvi1, homologous to the human IRAG gene, were also associated with enhanced platelet aggregation in human patients (38). In vivo it was revealed that IRAG is a NO/cGMP/PKG1-dependent factor which thereby inhibited arterial thrombosis (2).…”
Section: Irag As Pkg Target: Signaling and Functionmentioning
confidence: 97%
“…Recently, Jones et al (26), used a functional genomics approach to compare a relatively large number of SNPs (n = 1,327) in a selected group of candidate genes (n = 97), resulting in the identification of 17 independently associated SNPs that account for 48% of the variation in platelet reactivity induced by ADP. Even more recently, Johnson et al (27) performed a genome-wide meta-analysis of 2.5 million SNPs in 4,831 subjects to identify three loci associated with ADP-induced platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%